Bicytopenia and leukoerythroblastosis: a rare initial presentation of signet ring cell gastric adenocarcinoma - Vilma Takayasu; Edna Harumi Goto; Mayra Zanon Casagrande; Paulo Guilherme de Arruda Miranda; Gabriela Bezerra de Freitas Diniz; Micaela Frasson Monteiro; Aloisio Felipe-Silva (University of São Paulo, 2017)
Gastric adenocarcinoma is a common neoplasia and is responsible for up to 30% of the overall deaths due to cancer. Advanced disease is mostly characterized by peritoneum, liver, and lung involvement. The spread of the disease to the bone is rare, and bone marrow dissemination is even rarer. In this setting, leukoerythroblastosis may be the initial manifestation of the disease. The authors report the case of a 64-year-old Caucasian man who sought medical care complaining of back pain, weakness, and weight loss. The physical examination revealed pallor, and the laboratory work-up depicted severe anemia and thrombocytopenia; the peripheral blood smear was consistent with leukoerythroblastosis. The ongoing investigation through a bone marrow biopsy showed massive involvement of the bone marrow by a signet ring cell adenocarcinoma. During hospitalization, the patient presented melena, and an upper digestive endoscopy depicted an ulcerated and infiltrative lesion in the cardia, upon which the histological examination revealed a signet ring cell adenocarcinoma. This case highlights the bone marrow invasion represented by bicytopenia and leukoerythroblastosis as the initial manifestation of this histological type of gastric cancer. Although treatment attempts were made with chemotherapy and radiotherapy, the patient died early on, showing the aggressive behavior of this form of tumoral presentation